Angiotensin Converting Enzyme Inhibitor Has a Protective Effect on Decompression Sickness in Rats - Mazur, Aleksandra; Guernec, Anthony; Lautridou, Jacky; Dupas, Julie; Dugrenot, Emmanuel; Belhomme, Marc; Theron, Michael; Guerrero, François (Frontiers in Physiology, 2018)
Introduction: Commercial divers, high altitude pilots and astronauts are exposed to some inherent risk of decompression sickness (DCS), though the mechanisms that trigger are still unclear. It has been previously showed that diving may induce increased levels of serum angiotensin converting enzyme. The renin angiotensin aldosterone system is one of the most important regulators of blood pressure and fluid volume. The purpose of the present study was to control the influence of angiotensin II on the appearance of DCS. Methods: Sprague Dawley rats have been pre-treated with inhibitor of angiotensin II receptor type 1 (losartan; 10 mg/kg), angiotensin-converting enzyme inhibitor (enalapril; 10 mg/kg) and calcium-entry blocker (nifedipine; 20mg/kg). The experimental groups were treated for four weeks before exposure to hyperbaric pressure while controls were not treated. 75 rats were subjected to a simulated dive at 1000kPa absolute pressure for 45 min before starting decompression. Clinical assessment took place over a period of 60 min after surfacing. Blood samples were collected for measurements of TBARS, interleukin 6 (IL-6), angiotensin II (ANG II) and angiotensin-converting enzyme (ACE) Results: The diving protocol induced 60% DCS in non treated animals. This ration was significantly decreased after treatment with enalapril, but not other vasoactive drugs. Enalapril did not change ANG II or ACE concentration, while losartant decreased post dive level of ACE but not ANG II. None of the treatment modified the effect of diving on TBARS and IL-6 values. Conclusion: Results suggests that the rennin angiotensin system is involved in a process of triggering DCS but this has to be further investigated. However, a vasorelaxation mediated process, which potentially could increase the load of inert gas during hyperbaric exposure, and antioxidant properties were excluded by our results.